Proanthocyanidins Protect Against Cadmium-Induced Diabetic Nephropathy Through p38 MAPK and Keap1/Nrf2 Signaling Pathways - Gong, Pin; Wang, Peipei; Pi, Sihui; Guo, Yuxi; Pei, Shuya; Yang, Wenjuan; Chang, Xiangna; Wang, Lan; Chen, Fuxin (Frontiers in Pharmacology, 2022)
Diabetic nephropathy (DN) is one of the most devastating complications of diabetes mellitus. Although cadmium (Cd) exposure might be involved in the pathogenesis of DN, the underlying mechanism is still unclear. In this study, we explored the protective effects and possible mechanism of proanthocyanidins (OPC) from grape seed using a mouse model of Cd-induced DN. The successful establishment of this model was verified by analyzing the physiological and biochemical indices of mice, including their body weight and tissue ratio; levels of blood glucose, creatinine, microalbumin, total cholesterol, triglycerides, high-density lipoprotein-cholesterol and low-density lipoprotein-cholesterol; and was based on histopathological examination. Oxidative-antioxidative status, elemental analysis, and key signaling pathway analysis were performed to explore the possible protective mechanism of OPC. The protective effects of OPC and its possible mechanism in preventing the progression of DN were investigated using a multidimensional approach, including its ability in regulating oxidative-antioxidative status (lipid peroxidation, protein carbonyl, superoxide dismutase, and glutathione,GST, GSH-Px), metal-binding ability (Cd levels in the kidneys and urine and MT content) and mediation of essential elements (Zn, Ca, Cu, and Fe levels in the kidneys), and activation of the p38 MAPK and Keap1/Nrf2 signaling pathways. OPC exhibited a significant renoprotective effect, attributed to the metal-chelating ability, anti-oxidative effect, and mediation of oxidative stress-related signaling pathway. These results highlight the potential of OPC in preventing or treating DN in humans and suggest the dietary intake of grapes, which are rich in polyphenols, for the prevention of type 2 diabetes mellitus and its complications.